Knowledge towards standard precautions among healthcare providers of hospitals in Amhara region, Ethiopia, 2017: a cross sectional study - Ayele Semachew Kasa; Worku Animaw Temesgen; Yinager Workineh; Tadesse Dagget Tesfaye; Sitotaw Kerie; Eden Amsalu; Solomon Emishaw Awoke (BMC, 2020)
Abstract Background Literatures revealed that healthcare-associated infections are still a great concern in many developing countries including in Ethiopia. Despite the development of detailed guidelines for infection control, they remain as a critical challenge for the public health sectors and the knowledge of standard precautions among healthcare workers in many developing countries is low and not properly applied. Hence, the present study tried to determine the level of knowledge about standard precautions among healthcare workers of Amhara region, Ethiopia. Methods Institutional based cross-sectional study was conducted on a randomly selected public hospitals of Amhara region, Northwest Ethiopia from March 01-April 01/2017. A multistage sampling strategy was utilized to select 795 sampled healthcare workers. Data were collected using pretested self-administered questionnaire. The collected data entered using EpiData Version 3.1 statistical software and analyzed using SPSS version 20 statistical package. After using binary logistic regression, multivariable logistic regression analysis used to form the model. Variables which had statistically significant association with the outcome variable (P < 0.05) were identified as significant in the multivariable logistic regression analysis. Results Almost half (49.2%) of the study participants were female healthcare workers. Three-fourth (74.3%) of the healthcare workers involved in the current study had good knowledge towards standard precautions. Good knowledge towards standard precautions refers to scoring correct responses to > 60% of knowledge items from the survey. Year of service (AOR: 0.27, 95% CI: 0.16 to 0.44), educational status (AOR: 1.7, 95% CI: 1.13 to 2.56) were among the predictor variables. In addition, physicians were 6.97 times more likely to be knowledgeable (AOR: 6.97, 95% CI 2.42 to 20.12) than laboratory technician/technology counterparts. Study participants working in medical, Gyn/obs, pediatrics wards, and OPD were about 2.23, 4.27, 2.81 and 2.52 times more likely to be knowledgeable than study participants working in surgical ward. Conclusions Overall, the majority of healthcare workers had good knowledge of standard precautions. But variation in knowledge was detected across healthcare workers by hospital type and ward/units. This may help to design a solution by prioritizing the problem.